Assessment on abandoned housing project: Impact and revitalization in Malaysia - Saidah An'nisaa, Salam; Nur Farhayu, Ariffin; Mohamad Idris, Ali; Noram Irwan, Ramli (Penerbit UTHM, 2023)
The housing development sector was a key factor in the growth of Malaysia’s economic income since 1970s due to rapid urbanization. Unfortunately, housing construction in Malaysia still facing the abandonment issues due to financial constraints and many other factors. Abandoned housing project give a huge impact to the environment and socio economic to the stakeholder involved directly or indirectly. The purpose of this study is to overview the impact of abandoned housing project and to study the best solution in preventing the issues. Through extensive literature review from previous study and semi-structured interview session with 10 expert panels, several factors and impacts had been listed. A qualitative research methodology was conducted for data collection through an extensive literature review, semi-structured interviews and discussions with expert panels. From the discussion, the abandoned housing project give an impact to all parties and the proper financial management, amend the development concept, study the market signal properly, amend the initial policy of housing development and finally takeover the problematic development by the government is the best solution in preventing it.